Immune thrombocytopenic purpura following mRNA-SARS-CoV-2 vaccination: a case report - Lozada Ramos, Heiler; Martínez-Vega, Ruth Aralí; García, Liliana Torcoroma (Revista Cuidarte, 2024)
Highlights• Cases of autoimmune diseases have been registered after vaccination with mRNA vaccines (BNT162b2 or mRNA-1273).• A case of immune thrombocytopenic purpura following mRNA-SARS-CoV-2 without any previous reports of thrombocytopenia or other hematologic disorders is presented.• The thrombocytopenia persisted and progressed to a chronic non-bleeding condition two years after the first vaccine dose administration, with episodes of temporary recovery of platelet counts.• Considering that the incidence of secondary ITP and other hematological disorders has significantly increased due to COVID-19 vaccination, a post-vaccination hemogram check could be a useful and inexpensive follow-up measure.Introduction: Herein, it is presented a case report of a Colombian adult male patient, without any previous report of thrombocytopenia or hematological disorders, who developed a mild and chronic paucisymptomatic immune thrombocytopenic purpura, a rare complication following SARS-CoV-2 m-RNA. To the best of our knowledge, this represents the first documented case in Colombia of immune thrombocytopenic purpura associated with mRNA vaccines (BNT162b2 or mRNA-1273), with a comprehensive 2-year clinical follow-up. Case Description: The patient received the initial and second doses of the mRNA BNT162b2 vaccine in June 2021, the first booster dose in November 2021 (mRNA-1273), and the second booster dose (mRNA BNT162b2) in June 2022. Thrombocytopenia (
Keywords: COVID-19; SARS-CoV-2; mRNA Vaccines; Immune Thrombocytopenic Purpura; Platelets